Politics of immigration - quotas of entrance and hidden economy - Gemma Larramona; Jesus Clemente; Fernando Pueyo (European Regional Science Association (ERSA), 2005)
In spite of the fact that in recent years there has been a growing interest for the hidden economy, little attention has been lent to its relation with the illegal immigration as a consequence of the establishment of quotas. The objective of this work is to analyze the effect of a change in the quotas of legal immigrants in the size of the legal and illegal migration, the underground economy, and in the incomes perceived by the workers. The main conclusions are that, as opposed to the short time, in the long-term equilibrium, an increment of the quota does not have effect on the size of the migration, but in the composition between legal and illegal. On the other hand diminishes the work destined to the management of the underground economy by the reduction of illegal immigrants in the stationary state, however the effect is positive in the short run by the "called effect” of illegal immigrants that carries an increment in the quota.
Keywords: 330